A case of congenital maldisposition of pelvic peritoneum & chronic retention of urine at term pregnancy (Bangladesh Medical Journal, 2014)
Mal disposition of peritoneum over abdominal organs were reported both in cadaver & in diseased persons; but no report was found particularly about mal disposition of pelvic peritoneum. We are sharing our experience of a rare cause of chronic urinary retention due to abnormal disposition of pelvic peritoneum, diagnosed incidentally during lower segment ceaserian section. A 23 years young lady admitted at her term pregnancy as a case of prolong labour with failure of descend of fetal head. A healthy female baby was delivered by ower segment ceaserian section. But the procedure was not so smooth, though she had no risk factors for adhesive disease or past abdominal surgery. The bladder was hugely distended & atonic without any sign of obstructed labour. The peritoneal reflection was near fundus of the uterus; thats why the bladder was pulled up along with the growing uterus. On further inquiry, she gave the history of incomplete voiding from her 28th weeks of pregnancy. The peritoneum over other pelvic organs was also found loosely attached. The abnormal disposition of peritoneum over bladder & uterus is absolutely benign congenital malformation; but the condition is not free from complication. DOI: http://dx.doi.org/10.3329/bmj.v42i3.19003 Bangladesh Med J. 2013 Sept; 42 (3): 89-91